High-fat diet fuels prostate cancer progression by rewiring the metabolome and amplifying the MYC program - David P. Labbé (Nature Portfolio, 2019)
Prostate cancer progression may be enhanced by a high-fat diet. Here the authors show that a diet high in saturated fats enhance the MYC-driven transcriptional program, a feature that independently predicts prostate cancer progression and death.